Vuosien 1906-1915 kielioppikomitean mietinnön vastaanotto - Karlsson, Fred (Virittäjä, 1998)
The response to the report of the 1906-1915 Committee on Grammar (englanti) 1/1998 (102) Fred Karlsson (Department of General Linguistics (University of Helsinki); fkarlsso@ling.helsinki.fi) THE RESPONSE TO THE REPORT OF THE 1906-1915 COMMITTEE ON GRAMMAR The key members of the 1906-1915 Committee on Grammar were E. N. Setl, as chairman, and members Ralf Saxn and Ivan Uschakoff. The background to the setting up of the Committee was the debate that had been continuing for several decades about the teaching of grammar within language teaching in schools. What actually prompted the Committee to be set up at this time was a booklet dealing with the implementation of language teaching delivered to the National Board of General Education in March 1905 by language teachers from Helsinki's Finnish reaalilyseo upper comprehensive school. Letters written by E. N. Setl and others shed light on the working methods of the Committee and the stages through which the work progressed. Ralf Saxn proves to be the main organising force within the Committee, and it was he who managed to get Setl to complete the work when the final stages of the report were being prolonged. It has been generally understood that the linguistically novel principles of the Committee's report were never applied in practice. The writer notes, however, that Ralf Saxn did actually apply the Committee's approach to the study of grammar in several textbooks: Finsk ordbjningslra ('Inflection in Finnish', 1912), Svensk sprklra fr skolans lgre klasser ('Swedish grammar for lower school grades', 1916), Modersmlet ('Swedish grammar for native speakers', 1917), Modersmlet (revised edition, 1919) and Ruotsin kielioppi oppikouluja varten ('Swedish grammar for secondary schools', 1923, together with Hannes Almark). After the report was submitted, the Senate Committee on Ecclesiastical Affairs requested a statement on it from the National Board of General Education. The Board, in turn, immediately requested statements on the report from all the country's approximately 150 schools, to be submitted by June 1, 1916. The statements came, but the National Board of General Education never gave its own statement to the Senate Committee. Contrary to what is generally believed, notes the writer, the work of the Committee on Grammar did actually receive an official decision. On March 20, 1941, the matter came up at a meeting of the National Board of General Education's secondary school division. The matter was raised by Martti Adolf Jakobsson, appointed educational counsellor in 1940. The decision in paragraph 1 of the minutes is brief: No longer any cause for action. The article refers to several reasons why the report was, in practice, buried. Researchers of classical languages directed fierce criticism at the report, especially in the statement issued by the Pedagogical Association in autumn 1915. Belief in the importance of general grammar teaching died down quietly in the early decades of the century, when communication-oriented language teaching (e.g. the reform method) gained popularity. Surprisingly few language researchers were interested in the report's linguistically advanced proposals. The majority of schools and language teachers criticised the report for being too theoretical, and doubted the possibilities of applying the report's ideas in practice. The National Board of General Education itself also took a cautious view of the reform of grammar teaching.